Textual Coups and Democratic Imaginings in Contemporary Brazilian Literature | Golpes textuais e imaginários democráticos na literatura brasileira contemporânea - Lehnen, Leila (Revista PHILIA | Filosofia, Literatura & Arte, 2021)
Abstract This essay examines how Brazilian literature has broached changes in the country’s political and social scenario since 2013. Literary production has not only considered socio-political upheavals such as the 2013 protests, the 2016 impeachment of President Dilma Rousseff, and, more recently, the assassination of Rio city council member Marielle Franco as well as the 2020-21 COVID-19 pandemic. Literature has also expanded the signification of “democracy,” broadening the democratic lexicon by employing a language of both demands and entitlements and dispute. By creating a democratic imaginary that oscillates between vindication and exigency, contemporary Brazilian literature delineates the tensions inherent to present-day democratic culture, poised between expanding rights and what scholars have called a "democratic erosion." Keywords: Democracy. Democratic Erosion. Literature. Poetry. Resumo Este ensaio examina como a literatura brasileira tem abordado mudanças no cenário político e social do país desde 2013. A produção literária não aborda apenas levantes sociopolíticos como os protestos de 2013, o impeachment da presidente Dilma Rousseff em 2016 e, mais recentemente, o assassinato da vereadora Marielle Franco e a pandemia COVID-19. A literatura também tem expandido o significado de “democracia”, ampliando o léxico democrático ao empregar uma linguagem de demandas, direitos e disputa. Ao criar um imaginário democrático que oscila entre a reivindicação e a denúncia, a literatura brasileira contemporânea delineia as tensões inerentes à cultura democrática atual, equilibrada entre a expansão de direitos e o que os estudiosos chamam de "erosão democrática". Palavras-chave: Democracia. Erosão Democrática. Literatura. Poesia